2012
DOI: 10.1038/onc.2011.618
|View full text |Cite
|
Sign up to set email alerts
|

Dual role of the ddx5/ddx17 RNA helicases in the control of the pro-migratory NFAT5 transcription factor

Abstract: Ddx5 and ddx17 are two highly related RNA helicases involved in both transcription and splicing. These proteins coactivate transcription factors involved in cancer such as the estrogen receptor alpha, p53 and beta-catenin. Ddx5 and ddx17 are part of the splicing machinery and can modulate alternative splicing, the main mechanism increasing the proteome diversity. Alternative splicing also has a role in gene expression level regulation when it is coupled to the nonsensemediated mRNA decay (NMD) pathway. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 73 publications
(96 reference statements)
1
48
0
Order By: Relevance
“…DDX5 and DDX17 mediated regulation of mH2A1 alternatively spliced isoforms influences expression of mH2A1-dependent downstream genes involved in redox metabolism (38). We therefore measured the effect of DDX5/17 depletion on the expression profiles of hydroxyacid oxidase 1 (HAO1), Rieske (Fe-S) domain containing (RFESD), and extracellular superoxide dismutase 3 (SOD3).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…DDX5 and DDX17 mediated regulation of mH2A1 alternatively spliced isoforms influences expression of mH2A1-dependent downstream genes involved in redox metabolism (38). We therefore measured the effect of DDX5/17 depletion on the expression profiles of hydroxyacid oxidase 1 (HAO1), Rieske (Fe-S) domain containing (RFESD), and extracellular superoxide dismutase 3 (SOD3).…”
Section: Figmentioning
confidence: 99%
“…It has been shown that DDX5 and DDX17 regulate the alternative splicing of the promigratory transcription factor nuclear factor of activated T-cells 5 (NFAT5) and the histone macroH2A1 (38). The human NFAT5 gene has known alternatively included exons 4 and 5.…”
Section: Figmentioning
confidence: 99%
“…(16), and p38␣ (35, 73), and phosphatases, including SHP-1 (74), contribute to signaling high NaCl-induced activation of NFAT5. In addition to its role in activating expression of osmoprotective genes, NFAT5 is also involved in biological processes that apparently do not involve hypertonic stress, including cardiac development and function (42), vascular smooth muscle migration (26), skeletal muscle myogenesis (47), cancer progression and metastasis (7,22), replication of HIV-1, HIV-2, and multiple simian immunodeficiency (53, 54), SFFVp virus replication (67), and expression of multiple Toll-like receptor-induced genes (5).Glycogen synthase kinase-3␤, GSK-3␤ (GSK3B), is a ubiquitously expressed serine/threonine kinase that was originally characterized as phosphorylating and inactivating glycogen synthase, the rate-limiting enzyme of glycogen synthesis (28). Since then, GSK-3␤ has been found to regulate a wide variety of biological processes such as function of neurons (29), immunological responses (63), cardiac hypertrophy (8), and cancer (43).…”
mentioning
confidence: 99%
“…(16), and p38␣ (35, 73), and phosphatases, including SHP-1 (74), contribute to signaling high NaCl-induced activation of NFAT5. In addition to its role in activating expression of osmoprotective genes, NFAT5 is also involved in biological processes that apparently do not involve hypertonic stress, including cardiac development and function (42), vascular smooth muscle migration (26), skeletal muscle myogenesis (47), cancer progression and metastasis (7,22), replication of HIV-1, HIV-2, and multiple simian immunodeficiency (53, 54), SFFVp virus replication (67), and expression of multiple Toll-like receptor-induced genes (5).…”
mentioning
confidence: 99%
“…Because of their role in critical signalling pathways that control cell fate (Baksh et al, 2002;Chuvpilo et al, 2002;Xanthoudakis et al, 1996), one would expect that disturbing NFAT signalling could impact carcinogenesis. Indeed, beside their role in the migratory and invasive capacities of breast cancer cells (Fougère et al, 2010;Jauliac et al, 2002;Yiu and Toker, 2006;Yoeli-Lerner et al, 2005;Germann et al, 2012), there is growing evidence for an active role of NFAT factors in carcinogenesis (Buchholz et al, 2006;Dejmek et al, 2006;Foldynová-Trantírková et al, 2010;Holzmann et al, 2004;Jönsson et al, 2002). However, beside these reports of a ''pro-cancer'' role, others are showing the ''anti-cancer'' capacities of NFAT factors (Glud et al, 2005;Lee et al, 2005;Wu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%